PEMODELAN LIQUID LOADING PADA RESERVOIR GAS KONDENSAT - Rachman Hakim, Andika
Gas condensate production activities in oil and gas industry are enormously related to the liquid loading problem. The purpose of this study give a new perspective to the readers about the proposed method to produce gas from gas condensate reservoir. Recovery Factor of a gas field is strongly influenced by numerous factors. In gas reservoir with depletion drive mechanism, Recovery Factor is affected by the phenomenon of liquid loading. When liquid loading happened in a gas well, the value of Recovery Factor is decrease into a lower value than a gas well without the liquid loading problem. To obtain a high Recovery Factor, deliquefication must be done into a gas well with the liquid loading problem. One of many techniques for deliqueficate the liquid is the proposed method, open and close regularly to the well when the liquid loading phenomenon happened or before the liquid loading phenomenon happened. This method is known as cyclic shut –in well method. With this method applied to the liquid loading gas well, liquid loading can be avoided with simple technique and low cost technique compared to the other deliquefication techniques because this solution only require a rate control for start and shut the well from the surface. This study is conducted by simulation that uses Petrel, Eclipse, Prosper for the development of the static model to the simulation in reservoir and tubing. From the reservoir simulation result, an analysis in Recovery Factor is performed for the feasibility in cyclic shut in well technique. Economic aspects are not involved in this study, only operational aspect is involved